The Effectiveness of Interactive Animation Media in Improving Conceptual Understanding in Physics Subjects at Assumption College Thonburi - Chansiri, Anurak; Thongchai, Kanya (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to examine the effectiveness of interactive animation media in enhancing students' conceptual understanding in Physics at Assumption College Thonburi. The research was motivated by the consistently low level of conceptual comprehension among students when learning abstract and complex Physics topics. A quantitative approach was employed using a quasi-experimental design involving two groups: an experimental group that utilized interactive animation media and a control group that received conventional instruction. A conceptual understanding test was administered as both pre-test and post-test. Data analysis using an independent t-test revealed a statistically significant difference in learning outcomes between the two groups. Students taught using interactive animations showed a marked improvement in their understanding of key Physics concepts such as motion, force, and energy. Furthermore, the use of interactive media positively influenced students' learning motivation and classroom engagement. These results indicate that technology-integrated instruction, particularly with animated media, can effectively support conceptual learning and address the challenges often encountered in traditional Physics education. The study recommends broader implementation of interactive animation media not only in Physics but also in other science subjects to improve educational outcomes at the secondary level.